2006
DOI: 10.1111/j.1365-2648.2006.03796.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of severe acute respiratory syndrome: relationship between commitment and intention to leave nursing

Abstract: Perceived risk to life from infection has a possible influence on the commitment/intention-to-leave model in hospital nurses caring for patients with severe acute respiratory syndrome, and this information can inform hospital and nursing managers about nurse retention following a severe acute respiratory syndrome outbreak and the management of commitment in the context of nursing human resources management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 27 publications
2
43
1
2
Order By: Relevance
“…Sage 52 found in that regard organizational commitment was strongly related to the aggregated duration of voluntary absence. Despite that organizational commitment is considered an important factor related to turnover intention, 8,[17][18][19][20][21][22] the findings of the present study did not show a relationship between affective neither continuous commitment and turnover intention. Among the three components of commitment, findings showed that normative commitment was the only negative predictor of nurses' turnover intention.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Sage 52 found in that regard organizational commitment was strongly related to the aggregated duration of voluntary absence. Despite that organizational commitment is considered an important factor related to turnover intention, 8,[17][18][19][20][21][22] the findings of the present study did not show a relationship between affective neither continuous commitment and turnover intention. Among the three components of commitment, findings showed that normative commitment was the only negative predictor of nurses' turnover intention.…”
Section: Discussioncontrasting
confidence: 84%
“…Researchers examined the effects of organizational commitment on nurses' turnover intentions in different countries such as United States, 8,18 Canada, 19 Taiwan 20,21 and Australia. 8,[18][19][20][21][22] A well state of physical and psychological health of nurses is a perquisite for providing a quality of nursing care. 8,[18][19][20][21][22] A well state of physical and psychological health of nurses is a perquisite for providing a quality of nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research suggests that intention to leave can be associated with an array of factors, including work overload, lack of social support [22][23][24], burnout [25], feelings of work-family conflict [26] or stress [25,27], low job satisfaction [25,[28][29][30][31][32][33][34], supervisory support [35], organizational commitment [36,37], organizational climate [38], the quality of care [34], dissatisfaction with salary or low pay [25,39], and few possibilities for development [40]. Evidence from several present studies highlighted that stress results in high absenteeism and turnover, and low retention of nurses, which consequently affect the quality of care provided [19,20].…”
Section: Intention To Leave and Stressmentioning
confidence: 99%
“…Our result showed that getting support from the family helped the nurses to identify more deeply with their hospitals and have a greater willingness to work with extra efforts. Willingness to take care of SARS patients not only requires positive attitudes, but also psychological support from the family (Chang et al 2006). The drastic effect of family support on PC deserves attention.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Many empirical studies had proved that employees' PC was a strong predictor of intent to leave the profession (Chang et al 2006;Nogueras 2006). Aranya, Pollock and Amernic (1981) adopted the definition and measure of PC, which was modeled after Porter et al's (1974) approach and substituted the word, 'organization' for 'profession'.…”
Section: Oc and Pcmentioning
confidence: 98%